Types and evolution of faults in the east area of the Wushi Sag, Beibuwan Basin - WU Kongyou; LIU Yulei; HU Desheng; LIU Yin; ZHANG Shuai; CUI Lijie (Dizhi lixue xuebao, 2021)
Affected by multiple stages of tectonic movements, the Wushi Sag in the Beibuwan Basin has formed complex internal structures. Accurately identifying the structural development characteristics of different stages has a great significance for oil and gas exploration. In this paper, we used the high-precision 3D seismic and drilling data to analyze the fault type, combination pattern, evolution rule and dynamic mechanism in the east area of the Wushi sag. The results show that under the influence of the regional stress of extension-strike-slip and weak compression caused by the interaction between the Pacific plate, the Indian plate and the Eurasian plate, three sets of extension-strike-slip-compression fault systems were developed in the east area of the Wushi sag, and 13 types of plane and profile fault combinations are identified. The formation and evolution of the fault system endured five main stages, including the initial weak rifting stage in the Paleocene, the main extension stage in the Eocene, the strike-slip and weak extension stage in the Early and Middle Oligocene, the strike-slip and weak compression stage in the late Oligocene, and the final stage since the Neogene.